Pengembangan Bahan Ajar Analisis Struktural Novel Awan Karya Syafrudin Pernyata pada Mata Pelajaran Bahasa Indonesia Tingkat SMA - Lumban, Yunita; Arifin, Syaiful; Mulawarman, Widyatmike Gede; Suhatmady, Bibit; Hudiyono, Yusak (Syntax Literate, 2025)
The purpose of this research is to describe, among other things: 1) the structural analysis of Robert Stanton applied to the novel Awan by Syafruddin Pernyata, 2) the instructional materials containing the structural analysis of the novel Awan by Syafruddin Pernyata, and 3) the effectiveness of the instructional materials developed from the structural analysis of the novel Awan by Syafruddin Pernyata. This study employs a reflective, recursive, design, and development (R2D2) model research method. This method is used to produce and test a product using instructional materials based on the structural analysis of the novel Awan by Syafruddin Pernyata. The results of the study show that the instructional materials based on the structural analysis of the novel Awan by Syafruddin Pernyata were validated by a content expert who gave a score of 79.25%, which falls into the "acceptable" category, and a media expert who gave a score of 96%, which falls into the "very acceptable" category. Therefore, the instructional materials developed are highly suitable for use by high school students. Furthermore, the lesson planning was assessed by an observer who gave a score of 80.14%, and another observer assessed the lesson implementation with a score of 87.16%. Based on these assessments, it can be concluded that the teaching process was conducted effectively. The effectiveness of the instructional materials based on the structural analysis of the novel Awan by Syafruddin Pernyata can be seen from the results of a small group trial, which showed a pretest score of 57 and a posttest score of 19, as well as a field trial with an average pretest score of 69.95 and a posttest score of 81.75, both falling into the "good" category. Based on these data, it is evident that the developed instructional materials have successfully contributed to improving students' learning outcomes, as seen from the comparison of pretest and posttest scores.